Lecturer Career Management at Muhammadiyah Higher Education in the Era of Pademi Covid-19 (Case Study at UM Jember): Manajemen Karier Dosen Di Perguruan Tinggi Muhammadiyah Di Era Pademi Covid-19 (Studi Kasus di UM Jember) - Wakit , Saipul; Rhain, Ainur (Universitas Muhammadiyah Sidoarjo, 2021)
The large number of lecturers in Indonesia is clear evidence that there is still a large number of people who choose lecturers as their profession and career. So that the career of a lecturer in a university requires serious and professional management. One of the lecturers' career management processes in tertiary institutions can be done with career management. The purpose of this study has concrete objectives, namely to identify and describe the planning, development and career decision-making processes of lecturers at Muhamamdiyah university in the Covid-19 Pademi Era. The research method used a qualitative approach with a case study design at UM Jember with data collection techniques through interviews, observation and documentation. Lecturer career management at the University of Muhammadiyah during the Covid-19 pandemic includes several stages, namely career planning, career development and career decision making. Each of these stages has an operational process with its own methods and objectives. In lecturer career planning, it is divided into two, namely individual and organizational career planning which consists of several processes, namely the planning phase, the briefing phase, the development phase and the evaluation phase. Of all the stages of career management during the Covid-19 pandemic above, starting from planning, development and decision making, it is not much different from the conditions before the pandemic. But what distinguishes it is in terms of the career development method which in its implementation uses an online system with virtual methods, geogle meet and room zoom.